A new hybrid evolutionary algorithm with MCDM for plant forecasting using FIS - Nasir, Januardi; Ramli, Azizul Azhar (Penerbit UTHM, 2017)
Large Indonesians are engaged in the agrarian sector, so the character of a climate and weather such as rainfall greatly affects the sustainability of its income. Climatic and weather factors are used for agricultural considerations, especially in determining the suitability of crop species to be cultivated somewhere. But the conditions of the weather often change, because the definition of weather itself covers a narrow area and at a short time, so every time will change.